PENGARUH METODE MORAL REASONING TERHADAP PENANAMAN KARAKTER NASIONALISME SISWA SD DALAM PEMBELAJARAN TEMATIK - An-Nisa Apriani; Ruwet Rusiyono (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
This research aims to determine the influence of moral reasoning method on elementary studentsâ€™ nationalism character development in thematic learning. This is a quasi experiment research with a nonequivalent control group design. The subjects of this research were fifth graders of Ngebel Kasihan State Elementary School. Ngebel Kasihan State Elementary School has two fifth grade classes, class V-A as the control group used a storytelling method, and class V-B as the experiment group used a morel reasoning method. The data collection techniques used were observation and interview. The data analysis used was t-test with a significance level of 0.05. The research results showed that there was a significant difference between nationalism character development using a moral reasoning method and a storytelling method. The difference was seen is all nationalism sub characters which include â€œBelief in the one and only Godâ€ value with the t test result = 0.155, â€œJust and civilized humanityâ€ value with the t test result = 0.129, â€œthe unity of Indonesiaâ€ value with the t test result = 0.405, â€œPopularism Led by Wisdom of Wisdom in Consultation / Representationâ€ value with the t test result = 0.529, and â€œSocial justice for all the people of Indonesiaâ€ value with the t test result = 0.608.